Diagnosis and therapies for patients with cerebral palsy over the past 30 years: a bibliometric analysis - Jiang, Lili; Yang, Weifang; Chen, Huai; Song, Huangcheng; Zhang, Song (Frontiers in Neurology, 2024)
Background: Currently, the incidence of cerebral palsy is high in newborns. However, the current methods for diagnosing and treating patients with cerebral palsy are complex and poorly targeted. Moreover, these studies lack the support of bibliometric analysis results. Objective: Our study focused on a bibliometric analysis of published papers on the diagnosis and treatment of patients with cerebral palsy. To analyze the status and trends of research on the diagnosis and treatment of patients with cerebral palsy , this study attempted to identify the primary authors, institutions, and countries involved. Additionally, we screened pathways related to cerebral palsy. Methods: The PubMed database was searched for publications on the diagnosis and treatment of patients with cerebral palsy between 1990 and 2023. R v4.2.2 and VOSviewer v1.6.18 software tools were utilized to perform this bibliometric analysis and visualization. Results: There were 1965 publications on cerebral palsy diagnosis and 5418 on treatment that qualified, and the annual number of publications increased. In this field, the United States dominated. Gregory Y.H. Lip and Patrizio Lancellotti published the most papers. The Cleveland Clinic published the most papers in the field. According to the analysis of the co-occurrence of keywords, we found that the main research directions were age, sex, disease diagnosis and treatment. Newly emerging research has focused mainly on heart failure, which is related to valvular heart disease.The findings presented in this study offer valuable insights into ongoing research and potential future directions pertaining to cerebral palsy. These insights can assist researchers in identifying suitable collaborators and enhancing their investigations aimed at identifying the underlying molecular mechanisms associated with cerebral palsy, encompassing its etiology, preventive measures, and therapeutic interventions.